Peasant communities in Peru: Organization, conflicts and collective action, Junín, 1959-2017 - Lázaro Aquino, Teódulo Gerardo (2024)
The objective was to analyze the processes of organization, action, leadership and perspectives of peasant communities in Peru, specifically in Junín, period 1959-2017, under a qualitative methodological approach, narrative-historical design. It is evident that in the 50s-60s of the 20th century, peasant organizations focused on the land problem with the estates, on the implementation of the pilot plan for agrarian reform and the founding of a communal university. Between 1969-1980, they were part of the structure of the Agricultural Societies of Social Interest, implemented by the agrarian reform of 1969. From 1980 and the end of the 90s, overwhelmed by political violence, the Peasant Rounds were formed, especially to confront the authoritarianism and Shining Path terrorism. In the 21st century, many communities continue the fight for territory with extractive companies (mining, hydrocarbons, non-metallic) and with the State for infrastructure and better public services.